At kende sin besøgelsestid - Steenbuch, Johannes Aakjær (Dansk Teologisk Tidsskrift, 2015)
The theology of the English Quaker Robert Barclay gives a rather different picture of Quakerism than does the somewhat antidogmatic and often liberal expressions of the modern versions of the movement. While emphasizing individual, inward revelation over outward creeds, Barclay’s thinking is at the same time rationalistic and systematic. This article discusses how the relationship between revelation and tradition plays out in the relation between the inward and the outward, the universal church and the particular church and more, and argues that Barclay’s thinking is compatible with an emphasis on the particular, tradition and community.